New Insight into Platinum Dissolution from Nanoparticulate Platinum‐Based Electrocatalysts Using Highly Sensitive In Situ Concentration Measurements. Issue 2 (20th December 2013) - Jovanovič, Primož; Pavlišič, Andraž; Šelih, Vid Simon; Šala, Martin; Hodnik, Nejc; Bele, Marjan; Hočevar, Samo; Gaberšček, Miran
Abstract Time‐ and potential‐resolved electrochemical Pt dissolution from commercial Pt and prepared PtCu alloy nanoparticulate catalysts have been studied under potentiodynamic conditions in 0.1 M HClO4 by using on‐line inductively coupled plasma mass spectrometry (ICP‐MS). For the first time the exact amount of dissolved Pt per cycle has been measured on real electrocatalysts. Results show clearly that Pt dissolution depends on the particle size: approximately seven times as much Pt is released into the solution from commercial 3 nm Pt particles as from a commercial 30 nm Pt sample. The stability of our prepared PtCu electrocatalyst is higher than that of a commercial 3 nm electrocatalyst, which is, however, still slightly lower than that of a commercial 30 nm Pt electrocatalyst.